Impact of corporate governance on bank effeciency: a study on selected licensed domestic commercial bank in sri lanka - Mathanika, T. (My University, 2016)
The special nature of banking business requires the implementation of more specific and complex mechanisms for banking governance. Banking governance is conceived primarily to establish an effective banking structure with full potentiality in the financing of the economy. This study is an attempt to investigate the impact of corporate governance on bank efficiency of listed licensed commercial banks in Sri Lanka. This research focused on secondary data collection method which information drawn from 8 licensed commercial banks during the period of 9 years from 2007 to 2015 on basis of Random sampling method. This study considered corporate governance as the independent variable which measured by Board size and Board Independence. The bank efficiency is considered as dependent variable which measured by Non performing loan ratio and Non performing assets ratio. In this research study used for Bank size as control Variables. The descriptive statistics are used and Pearson's correlation coefficient is used to identify the relationship between corporate governance and bank efficiency. The regression analysis is used to identify the impact of corporate governance on bank efficiency. The results of this study reveal that Board independence has a significant impact on NPLR of listed licensed commercial banks in Sri Lanka. It can be concluded that there is a positive relationship between corporate governance and bank efficiency also the banking system which efficiently channels financial resources to productive use is a powerful mechanism for economic growth.
Keywords: Bank efficiency; Board independent; Board size; Corporate governance; Listed licensed commercial banks; Non performing loan ratio; Non performing assets ratio